Settlement Of Goods/Services Procurement Contract Disputes - Windu Arista, Panji; Handayati, Nur (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2024)
This research aims to describe the dispute resolution process in public procurement contracts in Tangerang City. The research method is empirical juridical. The results show that there is a dispute in the implementation of the goods/services procurement contract in Tangerang City between the Tangerang City Public Works and Spatial Planning Agency and the goods/services provider during the 2021 fiscal year, namely in the form of a discrepancy between the remaining package capabilities submitted by the provider and the reality in the field. The settlement of the problem that occurred between the Tangerang City Public Works Office and the provider in dispute was through non-litigation channels by imposing a sanction of blacklisting the provider by the budget user of the Public Works and Spatial Planning Office in accordance with applicable regulations.